Outcome of multifaceted interventions for improving the quality of antenatal care in Nigerian referral hospitals - Friday Ebhodaghe Okonofua; Lorretta Favour Chizomam Ntoimo; Bola Ekezue; Victor Ohenhen; Kingsley Agholor; Mohammed Gana; Brian Igboin; Chioma Ekwo; Wilson Imongan; Hadiza Galadanci; Rosemary Ogu (BMC, 2020)
Abstract Background The study was designed as quasi-experimental research to investigate the effectiveness of multifaceted interventions for improving the quality of antenatal care in referral hospitals in Nigeria. Two referral hospitals (the Central Hospital in Benin City, South-South Nigeria, and the General Hospital in Minna) served as intervention sites, while two hospitals in comparable locations, (the Central Hospital Warri and the Suleja Hospital Abuja) were the control hospitals. Methods Intervention activities consisted of the introduction of a strategic plan with the shared vision of reducing maternal mortality by 50% in 1 year in the hospitals; staff training and re-training; the establishment of an automated appointment system; composite health education involving couples and providers; advocacy with policymakers; and the implementation of maternal death reviews and surveillance. These activities were implemented in the intervention hospitals over 21 months (October 2017 to June 2019). Exit interviews of pregnant women at intervention and control sites by trained interviewers were used to assess the quality of antenatal care after their visit, A total of 777 women were interviewed (427 in the intervention sites and 350 in the control sites). Data were analyzed with univariate and multivariate Poisson and logistic regression to determine the extent to which health providers in the clinics completed the 18 signal functions identified in the WHO assessment tool. Results The regression analyses showed the interventions were effective in improving six quality indicators (QIs) for counseling and information sharing. The difference between intervention and control sites on these QIs was significant at < 0.05. On the contrary, the interventions were less effective for maternal and fetal measurements; and disease testing and management QIs. Conclusion The positive effects of the interventions are likely due to the effectiveness of the training and health education components. The lack of intervention impact observed for maternal and fetal measurements may be due to the high workload of care staff and inadequate clinic supplies, which we did not address. We conclude that interventions that address the quality of antenatal care in low-resource settings should focus on improving all elements of care, including adequate staffing and mobilization of material resources. Trial registration This study was registered in the ISRCTN on August 14th, 2020. Trial Registration Number. SRCTN17985403 . Retrospective registration. The reason for the retrospective registration is the current non-recognition of the Nigeria Clinical Trials Registry (NCTR); which is currently not an ICMJE or WHO ICTRP approved registry. (This study was registered in the Nigeria Clinical Trials Registry on April 14th, 2016. Trial Registration Number NCTR No: 91540209 ).